PROSES MANUFAKTUR MESIN PENCACAH BATANG TANAMAN SORGUM UNTUK PAKAN TERNAK - Muhammad Isa Hadijaya, (2023)
Sorghum is a type of cereal plant that has a fairly high nutritional content which also has a high ability to tolerate dry conditions in the surrounding environment because this plant does not require a lot of water during its growth process, so that sorghum cultivation is increasingly being carried out, especially in areas that have a dry environment. Along with the increasing number of sorghum cultivation, the problem of processing waste material from sorghum cultivation in the form of sorghum plant stems also arises. The author carried out the process of designing a sorghum stem chopper machine with a research method that began with conceptual design, manufacturing analysis, and trials aimed at overcoming the problem of processing sorghum stems, namely by making a sorghum stem chopper machine that could chop 400 kg/hour stems. sorghum plants into pieces that have a length of 10-20 mm and a width of 1-5 mm so that these pieces can be used as nutritious feed for livestock. This chopping machine has overall dimensions of 65 cm x 40 cm x 140 cm and has 14 chopping blades made of ST37 Steel which are connected to the shaft where the shaft is connected by a transmission system in the form of a pulley and belt to a gasoline motor powered by 5.5 hp with a rotation of 1300 rpm. as a mover. Key words : Sorghum, chopper machine, livestock feed